Macrophage Activation Syndrome in Pediatric Systemic Lupus Erythematosus: A Systematic Review of the Diagnostic Aspects - Abdirakhmanova, Altynay; Sazonov, Vitaliy; Mukusheva, Zaure; Assylbekova, Maykesh; Abdukhakimova, Diyora; Poddighe, Dimitri (Frontiers in Medicine, 2021)
Macrophage Activation Syndrome (MAS) is a very severe complication of different rheumatic diseases, including pediatric Systemic Lupus Erythematosus (pSLE). MAS is not considered as a frequent complication of pSLE; however, its occurrence could be under-estimated. In order to address this issue, we performed a systematic review of the available medical literature, aiming to retrieve all those papers providing diagnostic (clinical/laboratory) data on patients with pSLE-related MAS, in individual or aggregated form. The selected case reports and series provided a pool of 46 patients, accounting for 48 episodes of MAS in total. We re-analyzed these patients in light of the diagnostic criteria for MAS validated in systemic juvenile idiopathic arthritis (sJIA) patients and the preliminary diagnostic criteria for MAS in pSLE, respectively. Additionally, 5 clinical studies were selected and used to support this analysis. This systematic review confirms that MAS diagnosis in pSLE patients is characterized by several diagnostic challenges, which could lead to delayed diagnosis and/or under-estimation of this complication. Specific criteria should be considered to diagnose MAS in different rheumatic diseases; as regards pSLE, the aforementioned preliminary criteria for MAS in pSLE seems to perform better than the sJIA-related MAS criteria, because of a lower ferritin cut-off.